On Some Popular Errors Concerning the Scope and Method of Economics – Part 2 - Mises, Ludwig von (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2014)
The text criticizes some common mistakes on the purpose and the appropriate method for economics. Points known fallacies, such as consider the economy as a zero sum game, the omnipotence of the human mind, the infallibility of majorities and the belief in a perfect system of government, among others. Finally, he shows the proper method for the sciences dealing with human action.